Metastatic melanoma: spontaneous occurrence of auto antibodies is a good prognosis factor in a prospective cohort. (7th December 2011) - Maire, C.; Vercambre‐Darras, S.; Devos, P.; D'Herbomez, M.; Dubucquoi, S.; Mortier, L.
Abstract Background Melanoma is an immunogenic tumour type frequently associated with spontaneous auto‐immune manifestations such as spontaneous regression, vitiligo‐like reactions or auto‐immune retinopathy, which seem to be associated with better prognosis. Objectives The aim of this prospective study was to evaluate the correlation between spontaneous autoimmunity and survival in patients with stage IV melanoma. Methods From 2007 to 2008, 103 patients were studied with antithyroid and antinuclear auto antibody assays performed every 6 months. Any detectable occurrence of a spontaneous self antibody (SpSA) at the upper detection limit, at least for one assay, was considered to be a biological marker of autoimmunity. Results Univariate and multivariate analyses confirmed significantly longer survival in the absence of known primary melanoma (P = 0.044) and in the presence of marker of biologic autoimmunity, independently of previous immunotherapy (P = 0.045). Conclusions This prospective and comparative study is, to our knowledge, the first to report the frequency of SpSA in stage IV melanoma. Our results suggest that spontaneous autoimmunity, through a rupture of self‐tolerance, is a good prognostic factor in a subgroup of patients with stage IV melanoma.